1987
DOI: 10.1159/000174192
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four-Hour Electrocardiographic Study in the Active Very Elderly

Abstract: Cardiac rhythm was studied by means of 24-hour ambulatory ECG in 18 active outpatients, mean age 92.3 ± 2.3 years. The main characteristics observed were the following: a broad dynamic heart rate range; relatively rare atrial fibrillation (5.5%); incidence of simple atrial and ventricular premature beats, complex atrial premature beats or supraventricular tachycardia in all subjects, while ventricular tachycardia and R-on-T phenomenon were present in only one subject. The ‘arrhythmic normality’ parameters in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The frequency and prevalence of PACs are known to increase with age. 29 As with PVCs, differences in study populations (older male), detection methods (24-hour monitoring) and outcomes (composite stroke) may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and prevalence of PACs are known to increase with age. 29 As with PVCs, differences in study populations (older male), detection methods (24-hour monitoring) and outcomes (composite stroke) may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PACs in that study was 19% compared to 4.9% in our study, while the stroke rate was 14% compared to 3.5% in our study. The frequency and prevalence of PACs are known to increase with age . As with PVCs, differences in study populations (older male), detection methods (24‐hour monitoring) and outcomes (composite stroke) may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Fleg et al [18] reported a PVC prevalence of 78% among 98 healthy people aged 60-85 years. Higher rates were reported in older groups, reaching 89.4% in a study by Garcia et al [19] including 94 healthy subjects aged 70 years and older, 96% in a study by Kantelip et al [20] in 50 people aged 80 years and older, and 100% in a study by Rossi et al [17] including 18 active subjects aged 90 years and older.…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence of PVC in the general population ranges from 4 to 20% and increases with age [14,15]. Studies conducted among active older people have shown that the prevalence of PVC varies 69-100% [16,17]. Fleg et al [18] reported a PVC prevalence of 78% among 98 healthy people aged 60-85 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation